Drama-Theoretic Analysis of Asymmetric Trade Negotiation - Allya Ghina Syafira Wini; Pri Hermawan (Eduvest - Journal of Universal Studies, 2026)
In relation to the asymmetric trade between Indonesia and the United States, this study examines the dilemmas faced by Indonesia during reciprocal tariff negotiation with the United States which had resulted in seemingly unbalanced outcome. First, this study aims to analyse potential dilemmas that emerge in asymmetric bilateral negotiation. The dilemmas that might occur are dilemma of cooperation, dilemma of trust, dilemma of positioning, dilemma of persuasion, dilemma of rejection, and dilemma of threat. Then, this study uses position-and-threats two-parties negotiation simulation, payoff-matrix analysis to identify the Nash equilibrium, and dilemma analysis to analyse the negotiation dynamics. Next, after the analysis the study shows that in asymmetric bilateral trade negotiation between Indonesia and the United States, Indonesia faces dilemma of trust, dilemma of persuasion, dilemma of rejection and dilemma of threat. These dilemmas were caused by the weaker bargaining position Indonesia has and high reliance on the United States position. Finally, this study suggests that weaker countries like Indonesia to strengthen their Best Alternative to a Negotiated Agreement (BATNA) and create stronger coalitions to reduce such dilemmas, which could improve the negotiation outcomes. The recommendations highlight the importance of strong and strategic coalition and better BATNA management strategy to achieve more balanced agreement in future asymmetric negotiation.